A Mechanism Design Approach to Planning Problems in Intermodal Transport Logistics of Large City Sea Ports and Megahubs - Kress, Dominik; Meiswinkel, Sebastian; Nossack, Jenny; Pesch, Erwin (Springer, 2018)
Globalization and digitalization have lead to new challenges and perspectives in intermodal transport logistics of large city sea ports and megahubs. In particular, due to an enormous increase of the container throughput over the last decades and the automatization of megahubs, new planning problems in this field must consistently be addressed by smart software solutions. In this research article, we sketch some challenges that arise at megahubs and outline how mechanism design, as a popular tool that combines ideas from game theory and computer science, can be an approach to tackle logistics problems that involve multiple selfish players.
Keywords: Stadt; Seehafen; Wirtschaft; Transport; Globalisierung; Digitalisierung; Transportlogistik; Containerterminal